A Multilevel View of the Development of Alzheimer's Disease. (1st March 2021) - Avila, Jesús; Perry, George
Highlights: Examination of Alzheimer's disease at different levels and at different stages of its development. Comment on clinical diagnosis, brain damage, brain networks and cellular/molecular markers. Focus on the early developmental stages (time is important). Correlation over time of some features at different levels of analysis. Comment on a possible working hypothesis related to the development of the disease. Abstract: Every year the Alzheimer's Association publishes a report that provides facts and figures indicating the public health, social and economic impact of Alzheimer's disease (AD). In addition, there are a number of reviews on the disease for general readers. Also, at congresses, AD is analyzed at different but not always related levels, leading to an "elephant as seen by blind men situation" for many of the participants. The review presented herein seeks to provide readers with a holistic view of how AD develops from various perspectives: the whole human organism, brain, circuits, neurons, cellular hallmarks, and molecular level.